Peran Kepemimpinan Kepala Desa Dalam Meningkatkan Kedisiplinan Kerja Perangkat Desa di Desa Cintakarya, Kecamatan Sindangkerta, Kabupaten Bandung Barat - Frizi, Feby Reyhan; Tresnawati, Amilia (Jurnal Ilmu Komputer dan Bisnis, 2026)
This study aims to examine the role of the Village Head in enhancing work discipline among staff members at the Cintakarya Village Office. The research centers on identifying actions and policies taken by the Village Head to foster a culture of responsibility and discipline among village officials. The leadership role is viewed as essential in establishing a productive work environment and ensuring compliance with established rules. A qualitative descriptive method was employed in this research to provide an in-depth understanding of the phenomena. Data collection techniques included direct observation, in-depth interviews with relevant stakeholders, and documentation review. The data were analyzed through three key steps: data reduction, data presentation, and drawing conclusions based on the patterns identified in the findings. The results of the study indicate that the Village Head significantly influences the improvement of work discipline among village officials. This is reflected in better attendance, reduced tardiness, and greater adherence to job responsibilities. A leadership style that emphasizes communication and collaboration has proven to be a critical factor in supporting this improvement. Keywords: Leadership, Work Discipline, Village Officials